Dietary exposure of the Portuguese Population to Nitrates based on a Total Diet Study - Vasco, Elsa (2022)
Aim: The objective of this study was to assess the dietary exposure of the adult Portuguese population to nitrates and the risk concerning the acceptable daily intake (ADI) healthbased guidance value as reference.